Konsep Kejujuran Al-Qur’an dalam Pendidikan Karakter dan Pembinaan Akhlak Modern: Akhlak Masyarakat Modern; Pedoman Al Qur'an - Wahyu Nurul Fitri; Amri Muammar; Nurul Faizah; Maria Stela Febry Kodoatie; Abbas .; Ahmad Nashir (CV. ITTC INDONESIA, 2026)
One of the main moral principles in Islamic teachings is the value of honesty (ṣidq), which plays a vital role in building one's character and fostering morality in society. The purpose of this study is to examine the concept of honesty from the perspective of the Qur'an and how it is applied in character education and moral development in modern society. Quranic verses, hadith, classical and contemporary commentaries, as well as relevant scientific literature and previous research served as the data sources for this study, which was conducted using qualitative methods and a librarian research approach. The results show that, from the Qur'an's perspective, honesty encompasses personal, social, and spiritual aspects, and that noble character is an essential component of honesty. This study concludes that the value of honesty in the Qur'an is universal and relevant for character education and moral development in modern society. This study provides a conceptual basis for the development of applicable character education strategies and opens up opportunities for further study on the integration of Quranic values ​​in the formation of a society with noble character.